MSME initiatives to support cloud adoption in India. (14th September 2020) - Shetty, Jayalaxmi P.; Choudhury, Dibyendu; Panda, Rajesh
The purpose of this article is to determine how effectively Digital-MSME can be implemented with the help of Digital India program and outline recommendations for its successful implementation to support cloud adoption in Indian small and medium enterprises (SMEs). Using case research approach by theory elaboration method, the authors modify the general theoretical framework and validate it empirically through eight depth interviews with senior ministry officials, cloud service providers and industry peers. The analysis sheds light on well-designed policies and shows Digital India program as a positive platform for bridging the generation and the diffusion side of initiatives. The findings have added a dimension of nodal points for the benefit of stakeholders to optimise cloud implementation. The paper prompts technical diffusion both in individuals and in businesses. Value is added in linking the generation side of policies with that of diffusion through participatory governance and participatory citizenry.